Threats and opportunities for workplace ergonomics in lean environments - Arezes, P. (2010)
Lean Management Systems (LMS) have become very popular among the manufacturing industry, services and large commercial areas. A LMS must develop and consider a set of work energizers to bring compatibility with workplace ergonomics, namely at a muscular, cognitive, and emotional demands level. The goal of this study is the identification of the most relevant impacts of a LMS adoption from the ergonomic point of view and cited in the literature and the synthesis of some possible drawbacks in workplace ergonomics due to a flawed application of the LMS. A final discussion about the most important, positive and negative, impacts are present at the end of the paper.